Achieving Sustainable Development through Non-Oil Sector Development: Is this feasible in Nigeria? - Charles O. Manasseh; Chine Sp Logan; Kenechukwu K. Ede (Indonesian Journal of Sustainability Accounting and Management, 2024)
The aim of this study is to analyze the contribution of non-oil sector development in fostering sustainable development in Nigeria, utilizing time series data from 1986 to 2018. The study used pairwise granger causality and OLS estimation techniques to determine the impact of non-oil sector development (agriculture, manufacturing, and services) in supporting sustainable development, as measured by unemployment and poverty rates. The pairwise granger causality results reveal that agriculture output, industrial output, and service sector output all have unidirectional causality with unemployment and poverty rates. The findings of the OLS estimate indicated that the components of non-oil sector development are significant and negatively associated to sustainable development in Nigeria. The results also offer the foundation for arguing the postulate of resources cause theory, which states that countries endowed with non-renewable natural resources typically experience sluggish economic growth and development. Thus, this imply that non-oil sector development is a crucial predictor of Nigerias sustainable development. As a result, we urge that the Nigerian government increase its investment in the agricultural, manufacturing, and service sectors.